2012
DOI: 10.4236/ojpm.2012.22029
|View full text |Cite
|
Sign up to set email alerts
|

The community capacity building for sustainable dengue problem solution (CCB-SDPS) model: The results from studies in community, southern region, Thailand

Abstract: This paper provides an approach for sustainable dengue problem solution by the community capacity building model and the results of two studies from implementation the model in Southern region, Thailand. The conceptual framework of the CCB-SDPS model consisted of three dimensions; 1) community-based (leader and nonleader in community), 2) community capacity building process, and 3) sustainable dengue problem solution (outcomes). The outcomes of studies focused on the capacity level by the DCCAT (14 domains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Implementation of all community members of the school and activate the larva examiner health business program student as an effort to reduce the cycle of dengue transmitter reproduction by empowerment which is done by increasing the knowledge and skills of vector control. This is in line with the research conducted by Chanuai Suwamnbamrung, 11 suggests that community and community leaders can lower the entomology vector indicator of Dengue Hemorrhagic Fever that is house index (HI), container index (CI) and breteau index (BI) and build sustainability ) program.…”
Section: Numerical Density Ratesupporting
confidence: 84%
“…Implementation of all community members of the school and activate the larva examiner health business program student as an effort to reduce the cycle of dengue transmitter reproduction by empowerment which is done by increasing the knowledge and skills of vector control. This is in line with the research conducted by Chanuai Suwamnbamrung, 11 suggests that community and community leaders can lower the entomology vector indicator of Dengue Hemorrhagic Fever that is house index (HI), container index (CI) and breteau index (BI) and build sustainability ) program.…”
Section: Numerical Density Ratesupporting
confidence: 84%
“…Notably, the author suggested that in cooperation of similar programs for prevention of dengue through behavioural change to the public health system of Sri Lanka seems feasible and cost effective (Wijesundara, 2009). Moreover, a community-based dengue prevention and control process enables key stakeholders in the community to actively prevent and control their dengue problem (Suwanbamrung, 2012). Therefore, the present study was based on COMBI method after conducting situation marketing analysis by quantitative evaluation and FGD among volunteers in the community, healthcare workers and non-health sector stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…al, 2004), Colombia (Luna et. al, 2004), Hulu Langat (Rozhan, 2006) and Thailand (Suwanbamrung, 2012) revealed that the interpersonal communication is an effective way to achieve greater success of a community-based programme. Therefore, the present study aimed to empower the community by developing a sustainable dengue control process at the grass root level with the involvement of multi-stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation